POLICY ANALYSIS OF THE DEVELOPMENT OF SMALL AND MEDIUM COFFEE INDUSTRIES IN SOLOK DISTRICT (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
Regional autonomy policy, giving authority to the government of Solok District to formulate and establish policies for the development of small and medium coffee industries (SMIs Coffee). The purpose of this study is to describe the policy for the development of the SMIs coffee in Solok District and provide ideas for the development of the SMIs in Solok District. The research used a qualitative descriptive method. Data were collected by conducting in-depth interviews and Desk Study. The variables observed in the research are central government policies in the form of Laws and Government Regulations concerning industrial development, particularly on SMIs. The local government policies studied are Regional Regulations and Regent Regulations concerning the development of SMIs coffee in Solok District. For the development of SMIs, the central government has issued Law No. 3/2014 concerning industry and Government Regulation No. 29/2018 concerning industrial empowerment, wherein this policy, the central government asks local governments to develop small and medium industries (SMIs) so that they have competitiveness. However, the current condition of the District Government of Solok does not yet have a Regional Regulation on the development of SMI) Coffee and other SMIs. The policy that Solok District already has is the Decree of the Regent of Solok No. 510-265-2018 concerning the Development of SMIs Clusters. The SMIs cluster which is prioritized in the Solok Regent Decree is the category of Food SMIs and Craft SMIs, while Coffee SMIs do not yet exist. To develop the downstream coffee that has been carried out by SMIs in Solok District, the local government of Solok District needs to do 4 important things, namely formulating and establishing policies in the form of regional regulations, strengthening institutional capacity, providing facilities and establishing digital marketing clinics for Coffee SMIs.